Nasal Foam Packing for Epistaxis: What are the Ideal Characteristics? - Serafini, Flavio; Araújo, Isabele Campos; Minhoto, Flavia; Santos, Ana Luiza Figueira (International Archives of Otorhinolaryngology, 2025)
Epistaxis is a common otorhinolaryngological emergency, usually caused by digital trauma in children, and hypertension in the elderly. General practitioners in emergency rooms assist most of the cases without specific management.Describe suitable properties for efficient nasal packing in adult epistaxis.Two cadaver heads, preserved by freezing process, were thawed for this research. When the room temperature was reached, the nasal cavities were evaluated by a nasal endoscope, which showed a length of 4.0 × 11.0 cm for the male and 4.0 × 8.5 cm for the female head. Through an orifice made in the left maxillary bone to access the maxillary sinus, a blue-dyed saline solution was applied using a sphygmomanometer (Premium) to control and mimic blood pressure. The nasal cavity was first packed with two foams with different thicknesses and densities evolved by a condom, then packed by the Merocel packing (Medtronicent Surgical Products Inc.). The pressure was administered and gradually increased until a saline leak was observed in the oropharynx. The best way to insert tampons was also evaluated to avoid extensive trauma.Despite the difficulty of the application being similar in both nasal packings made with the condom and foam, t33-densityity foam, 2.0 cm thick and 11.0 cm lon resisted to a higher pressure (250mmHg) than the commercial packing Merocel (220mmHg).The most suitable foam for packaging wrapped with condoms is 2.0 cm thick, as it supported the blood pressure commonly found in epistaxis.
Keywords: tampons; epistaxis; hypertension